Syntheses and crystal structures of 4-(4-nitrophenyl)piperazin-1-ium benzoate monohydrate and 4-(4-nitrophenyl)piperazin-1-ium 2-carboxy-4,6-dinitrophenolate - Holehundi J. Shankara Prasad; Devaraju; Vinaya; Hemmige S. Yathirajan; Sean R. Parkin; Christopher Glidewell (Acta Crystallographica Section E: Crystallographic Communications, 2022)
Crystal structures are reported for two molecular salts containing the 4-(4-nitrophenyl)piperazin-1-ium cation. Co-crystallization from methanol/ethyl acetate solution of N-(4-nitrophenyl)piperazine with benzoic acid gives the benzoate salt, which crystallizes as a monohydrate, C10H14N3O2·C7H5O2·H2O, (I), and similar co-crystallization with 3,5-dinitrosalicylic acid yields the 2-carboxy-4,6-dinitrophenolate salt, C10H14N3O2·C7H3N2O7, (II). In the structure of (I), a combination of O—H...O, N—H...O and C—H...O hydrogen bonds links the components into sheets, while in the structure of (II), the supramolecular assembly, generated by hydrogen bonds of the same types as in (I), is three dimensional. Comparisons are made with the structures of some related compounds.